Twelve years of activity of the International Trichinella Reference Centre - Pozio E.; La Rosa G.; D'Ancona F.; Amati M.; Mancini Barbieri F.; De Giacomo M. (Parasite, 2001)
The ITRC is the official reference laboratory of both the International Commission on Trichinellosis (since 1988) and the International Office of Epizootics (since 1992). The ITRC was created as a repository for Trichinella strains and as a source of materials and information for international research in 1988. To date, about 900 isolates of human and animal origin from throughout the world have been examined and identified by new procedures developed at the ITRC or in collaboration with other institutions. Using material from this collection, the ITRC has provided a complete revision of the systematics of the genus Trichinella. The ITRC database can be consulted by accessing the web-site: www.simi.iss.it/trichinella/index.htm.